ASTROPHYSICAL CONSTRAINTS ON MASSIVE UNSTABLE NEUTRAL RELIC PARTICLES - Ellis, J; Gelmini, G; Lopez, J; Nanopoulos, D; Sarkar, S (1992)
There has recently been renewed interest in massive neutral dark-matter particle candidates with masses greater than ∼ 1 TeV which may be unstable. We re-evaluate the constraints on such particles from the possible effects of their decays on the spectrum of the microwave background-radiation and the primordially synthesised abundances of the light elements, from observations of the diffuse gamma-ray background radiation, and from searches for muons and neutrinos in nucleon-decay and cosmic-ray detectors. We find that such unstable neutral relics may well have the cosmological critical density if their lifetime exceeds ∼ 1016 yr. We illustrate our arguments by applying them to technicolour baryons and to "cryptons" in superstring-inspired models. © 1992.